Video laryngoscope-guided urethral catheterization in female minipigs. (October 2022) - Li, Dawei; Liu, Zhaoxing; Zang, Yu; Ma, Jinglong; Zhang, Wen; Liu, Xinzhu; Zhang, Bohan; Shen, Chuan'an
Objective: The objective of this work was to anatomically locate the urethral orifice in female minipigs and describe the use of video laryngoscopes in urethral catheterization. Methods: Urethral catheterization guided by a video laryngoscope was attempted in 16 adult female Bama minipigs. The anatomical location of urethral orifices, operating time and complications (mucosal edema and bleeding in the vaginal vestibule, and the numbers of red blood cells (RBCs) and white blood cells (WBCs) in mid-stream urine samples) were recorded. Results: The anatomical location of the urethral orifice: the depth of the urethral orifice in female Bama minipigs was 4.2 ± 1.2 cm; all the urethral orifices were covered by mucosal folds of the vaginal vestibule. In the supine position, the orifice of the urethra at 9–12 and 1–3 o'clock accounted for 6.25%, 6.25%, 18.75%, 50%, 12.5%, 6.25% and 6.25%, respectively. All animals were successfully catheterized and the operating time was 9.0 (6.0–12.8) min. Complications: no bleeding in the vaginal vestibule was observed; the incidence of mucosal edema was 12.5%, all of which were mild; of urine samples collected 1 h after catheterization, 12.5% were found to contain RBCs and no RBCs were detected 6 h after catheterization; no WBCs were detected 1 h or 6 h after catheterization. Conclusions: The urethral orifice of female minipigs was located deep in the vagina at variable clock directions and was unexceptionally covered by mucosal folds. Applying a video laryngoscope in urethral catheterization allowed quick and accurate exposure of the urethral orifice and minimal operational injury in female minipigs.